THE ROLE OF DIGITALIZATION IN ENHANCING EFFICIENCY AND TRANSPARENCY OF THE SOCIAL SECURITY SYSTEM - Abramatova Surayyo G‘ofur qizi; Tangirov Irgash Khakkulovich (Modern American Journals, 2025)
The interrelation and mutual influence between digitalization and the social security system are considered one of the essential aspects of modern societal development. The advancement of modern technologies and digital infrastructures is fundamentally transforming social security systems, making them more efficient, rapid, and convenient for citizens. These processes not only improve public service delivery but also contribute to enhancing the quality of services in the field of social protection and expanding their coverage.
Keywords: Digitalization, social security, protection, service, data, organizations, corruption, society.